Kedudukan Kuitansi Dalam Sengketa Jual Beli Tanah Melalui Putusan Verstek - Roza, Widya; Yasniwati; Devianty Fitri (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2025)
The use of receipts as the primary means of evidence in land sale transactions remains prevalent due to practical considerations, low costs, and trust-based relationships, especially within familial or local community contexts. Legal complications arise when such transactions are not supported by an authentic deed from a Land Deed Official (PPAT), relying instead on a unilateral acknowledgment in the form of a private receipt. The issue becomes increasingly complex when adjudicated through a default judgment (verstek), as in Decision No. 2/Pdt.G/2022/PN Nab, in which the court accepted two receipts and the testimonies of witnesses who did not observe the transaction directly. This study examines the judicial considerations in assessing the probative value of receipts in default cases and evaluates the extent to which the principle of judicial prudence is applied. Employing a normative juridical method with a case study, statutory, and conceptual approach, the research adopts a descriptive-analytical framework based on library data. The findings indicate that a receipt, as a private unilateral document, carries limited evidentiary strength and attains full probative value only when acknowledged by the opposing party. Absent such acknowledgment, it constitutes merely preliminary evidence requiring corroboration. In default cases, the absence of the defendant cannot be interpreted as absolute admission, thus requiring the judge to rigorously and objectively evaluate all evidence presented. The study highlights the imperative of applying the principle of judicial prudence in default land sale cases to uphold legal certainty and safeguard the integrity of the evidentiary process